PHYSICO-CHEMICAL AND SENSORY EVALUATION OF CAPE GOOSEBERRY FRUITS (Physalis peruviana L.) - MÁRQUEZ C., Carlos J.; TRILLOS G., Ofelia; CARTAGENA V., José R.; COTES T., José M. (Vitae, 2009)
Cape gooseberry fruits are harvested at maturity for consumption at three different times. They are evaluated physico-chemically and sensorially. Repeated measures analysis are performed using a variancecovariance structure of the first order autoregressive heterogeneous. The results show statistically significant differences (p<0,05) for the variables (total soluble solids, acidity and pH), but not for the index of color and firmness, expressed as force of fracture. Through a panel of selected judges a sensory evaluation was performed which did not show statistically significant differences (p>0,05) for aroma, texture, mouth taste and flavors variables. The accesions studied for the phytoimprovement program of the physical, chemical and organoleptic characteristics were similar to the commercial samples. Therefore it is expected that crosses between them do not invalidate the exercise.